Variable Populations of Grapevine Virus T Are Present in Vineyards of Hungary - Demian, Emese (Viruses, 2021)
Grapevine virus T (GVT) is a recently described foveavirus, which was identified from a transcriptome of a Teroldego grapevine cultivar in 2017. Recently, we surveyed vineyards and rootstock plantations in Hungary using small RNA (sRNA) high-throughput sequencing (HTS), at a time when GVT had not yet been described. A re-analysis of our sRNA HTS datasets and a survey of grapevines by RT-PCR revealed the presence of GVT in most of the vineyards tested, while at rootstock fields its presence was very rare. The presence and high variability of the virus in the country was confirmed by sequence analysis of strains originating from different vineyards. In this study, we demonstrate the presence of GVT in Hungary and show its high diversity, suggesting that GVT presence may not seriously affect grapevine health and that it could have been present in European vineyards for a long time as a latent infection.